2017
DOI: 10.1371/journal.pone.0177688
|View full text |Cite
|
Sign up to set email alerts
|

Group participants’ experiences of a patient-directed group-based education program for the management of type 2 diabetes mellitus

Abstract: ObjectiveThe objective of this study was to explore the experiences of individuals who participated in a group-based education program, including their motivators in relation to their diabetes management, and the perceived impact of group interactions on participants’ experiences and motivation for self-management. Understanding individuals diagnosed with diabetes experiences of group-based education for the management of type 2 diabetes mellitus may guide the development and facilitation of these programs.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
1
13
0
3
Order By: Relevance
“…Thirteen of the included interventions were group‐based programmes and might have benefited from the unmeasured impact of group dynamics and peer support on outcomes, although the associated reports did not describe group dynamics . Six interventions were framed as individual programmes .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of the included interventions were group‐based programmes and might have benefited from the unmeasured impact of group dynamics and peer support on outcomes, although the associated reports did not describe group dynamics . Six interventions were framed as individual programmes .…”
Section: Resultsmentioning
confidence: 99%
“…Isso posto, torna-se considerável instigar a formação de habilidades dos coordenadores de grupos de EAN, já que, segundo Odgers-Jewell et al 2 , eles influenciam significativamente os resultados da intervenção, pois estabelecem o tom dos grupos e direcionam os processos educativos. Compreende-se que a formação dessas habilidades deve ser assegurada pelas instituições de ensino, sendo o desenvolvimento de trabalhos em grupos uma forma de promovê-las.…”
Section: Discussionunclassified
“…Compreendendo que os resultados da intervenção de EAN são decorrentes da atuação profissional e da interação entre profissional e usuários, destacam-se, no processo de avaliação, as abordagens qualitativas e participativas 2,4,8 . Contudo, Vincha et al 4 averiguaram que profissionais da AB que utilizam essas abordagens em grupos de EAN conduzem-nas de forma indireta e não sistematizada.…”
unclassified
“…Previous research in the area has highlighted similar problems including that: interventions are not described in adequate detail; education themes are not standardized; and the professional background of educators and their training are often unclear . A qualitative study, which explored group participants’ experiences of a patient‐directed group‐based education programme for the management of type 2 diabetes, indicated that the provider played a significant role and can have a positive influence on participants’ knowledge, motivation, and their feeling supported or reassured . Further studies have identified the important role of the provider in setting the tone and guiding the direction of groups, which may influence participant outcomes .…”
Section: Discussionmentioning
confidence: 99%